2011
DOI: 10.1002/ppap.201000140
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology in the Early Stages of Plasma Polymer Film Growth from Amine‐Containing Monomers

Abstract: The manner by which plasma polymers grow in the very first stages of deposition is a topic which has been almost overlooked. We show using atomic force microscopy (AFM) and X‐ray photoelectron spectroscopy (XPS) that in the early stages of plasma deposition there are significant differences in the way plasma polymers grow from two amine‐containing compounds onto silicon wafers. By AFM it is shown that films grown from n‐heptylamine (HA) initially show ‘island‐like’ growth before a continuous smooth film is for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 30 publications
7
67
0
Order By: Relevance
“…1). Our published studies demonstrated that plasma polymer films of this thickness are continuous and pinhole free [33,39]. The choice of ACpp as an overlayer was based on previous biological in vitro studies on planar surfaces which showed that ACpp coatings significantly reduced the inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Our published studies demonstrated that plasma polymer films of this thickness are continuous and pinhole free [33,39]. The choice of ACpp as an overlayer was based on previous biological in vitro studies on planar surfaces which showed that ACpp coatings significantly reduced the inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…A key benefit of the technique is that it can be applied to any type of substrate material as the technique is practically substrate independent and no surface pre-modification is required [33][34][35][36]. In contrast, self-assembled monolayers (SAM) require specific starting materials, LBL requires charged surfaces with multiple layers, and atomic layer deposition (ALD) can produce limited surface chemistry [33]. Another advantage of using plasma polymerization is that it is pin hole free, and conformal thin films can be deposited by using a single step coating procedure [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that ppAA films are deposited as a continuous film, rather than island formation, even for the shortest polymerization times. [26,43] If ppAA films were initially deposited as islands, then the increase in the number of positively charged groups would be attributed to the growth of these islands and eventual joining. The XPS data in Figure 9 indicates the ppAA film increases in thickness, and therefore, it is proposed that the increase in the number of positively charged groups with increasing film thickness is due to penetration of dye into the ppAA film.…”
Section: Influence Of Polymerization Time On Surface Chemistry and Humentioning
confidence: 99%
“…Michelmore et al [66] noticed that films grown from n-heptylamine initially show "islandlike" growth before a continuous smooth film is formed. In contrast, films from allylamine grow smoothly from the very earliest stages.…”
Section: Precursor Type Effectmentioning
confidence: 99%
“…AFM can be used to study the way plasma polymers grow: AFM images have been used to show the surface morphology of the deposited films while varying the treatment time [66]. AFM analysis is useful, not only in a qualitative way but also for quantitative determinations, since it allows a 3D representation of the treated surface and quantifies the effects of the plasma-etching mechanism by calculation of the surface roughness (root-mean-squared roughness, R rms ) [44].…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%